Crohn's disease severity in familial and sporadic cases. Issue 1 (1st January 1999) - Carbonnel, F; Macaigne, G; Beaugerie, L; Gendre, J P; Cosnes, J
Abstract : Background: Having a relative with inflammatory bowel disease increases the risk for Crohn's disease but may also increase its severity in affected patients. Aims: To evaluate the influence of a family history on Crohn's disease course and severity. Methods: 1316 patients followed in the same unit were studied retrospectively. Age at onset, duration of illness, site, and extent of disease were determined in patients with and without a family history. Additionally, disease severity was estimated by the need for medical therapy (steroid and immunosuppressive requirement) and the frequency and extent of excisional surgery. Results: 152 (12%) patients had a family history of inflammatory bowel disease. Duration of follow up was longer in patients with a family history and there were more operations for perforating complications in familial cases. However, the importance of medical therapy, and the incidence and extent of excisional surgery were similar in familial and and sporadic cases. Kaplan-Meier estimated time to prescription of immunosuppressive drugs and first intestinal resection were similar in familial and sporadic cases. When the 152 patients with familial Crohn's disease were paired for sex, location of disease at onset, date of birth, and date of diagnosis with 152 patients with sporadic Crohn's disease, the disease severity remained similar in the two groups of paired patients. Conclusion: Patients with Crohn's disease and a family history of inflammatory bowel disease do not have a more severe course.